Use the distributive property to remove the parentheses, then simplify by combining like terms. 3(2s – 6) + 3 2/26/2014 | Abby from Los Gatos, CA | 2 Answers | 0 Votes Mark favorite Subscribe Comment Comments Thank you! I had this one correct, just verifying. 2/26/2014 | Abby from Los Gatos, CA Comment
Hi Abby, By using the distributive property, 3(2x-6)=3×2x-3×6=6x-18 3(2x-6)+3=6x-18+3 =6x-15 2/26/2014 | Shelly J. Comment
Hi Abby; 3(2x – 6) + 3 Let's distribute 3 within the parentheses... 6x-18+3 Combine like terms... 6x-15 2/26/2014 | Vivian L. Comment
Comments